The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1984-70332017v17n4a49
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional vegetables collected in Brazil: chromosome number and description of nuclear DNA content

Abstract: The aim of this study was to perform chromosome counts and nuclear

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…In this study, the diploid chromosome count of 2n = 44 and haploid chromosome count of n = 22 indicates a basic chromosome number of x = 11 thereby indicating a chromosome number of 2n = 4x = 44 for the green-stemmed and the red-stemmed Basella alba studied. This is in line with the reports of Silva et al (2017) for Basella alba species obtained from Brazil. The chromosome numbers obtained for the green-stemmed and red-stemmed Basella alba in this study contradicts those of Hanson et al (2005) who reported chromosome numbers 2n = 48, 41 and 44 for those obtained from England.…”
Section: Chromosome Studiessupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, the diploid chromosome count of 2n = 44 and haploid chromosome count of n = 22 indicates a basic chromosome number of x = 11 thereby indicating a chromosome number of 2n = 4x = 44 for the green-stemmed and the red-stemmed Basella alba studied. This is in line with the reports of Silva et al (2017) for Basella alba species obtained from Brazil. The chromosome numbers obtained for the green-stemmed and red-stemmed Basella alba in this study contradicts those of Hanson et al (2005) who reported chromosome numbers 2n = 48, 41 and 44 for those obtained from England.…”
Section: Chromosome Studiessupporting
confidence: 93%
“…It also contradicts the reports of Sperling and Bittrich (1993) who reported the basic chromosome number of x = 12 for B. alba. According to Silva et al (2017) the chromosome number 2n = 44 observed in B. alba may have been derived from descending disploidy from the number 2n = 4x = 48.…”
Section: Chromosome Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Em busca de maiores lucros e produtividade espécies cultiváveis ganham destaque em produção e pesquisa por apresentarem elevado valor comercial, ao mesmo tempo que espécies endêmicas perdem seu espaço natural e são negligenciadas na alimentação cotidiana (SILVA et al, 2017).…”
Section: Introductionunclassified